Analisa Dan Perancangan E-Service Portal Untuk Calon Mahasiswa Baru Pada Binus University - Suryani, Eli; Wijaya, Robby; Wijaya, Ricornus Pranata; Valentina, Novita Maria (ComTech: Computer, Mathematics and Engineering Applications, 2010)
The purpose of this study is to analyze and design the application of e-service portal to help Marketing BINUS university to improve the speed and ease of service for Prospect students with the integration of transaction and information services required prospective students, and can be presented in a personalized to adds its own interesting experience for user. It would create a competitive advantage of the University which also potentially triggering an increase in the number of intake students. The methodology used is the method of analysis, which reviews and interviews conducted directly to the field, distributing questionnaires, observing and analyzing the data and needs, and using the design method, which includes design of business models, user interface design and database design. Results to be achieved is a web portal, where the system can facilitate prospective students to obtain the desired information services in full, and with a presentation that can be personalized and make transactions easier and faster. Conclusions obtained are BINUS University can take advantage of e-service in a web portal for prospective new students as supporting its competitive advantage in the utilization of information technology and support one of its primary missions to create service excellence in all fields.